I can't stand losing you : examining the impact of affiliation motivation on political knowledge of Facebook users - Dasgupta, Priyanka (2017)
Using the Cognitive Mediation Model (CMM) as a framework, this dissertation examines the impact of affiliation motivation on political knowledge of Facebook users, in addition to the motivation and information processing variables already included in CMM. Affiliation motivation can be defined as the need to establish and maintain relationships. A systematic review was conducted to identify gaps in extant literature, which was followed by the administration of two surveys. First, the systematic review of academic articles examined motivations associated with political knowledge in extant research. Several motivations were identified including surveillance gratification. However, affiliation motivation has not yet been examined as a predictor for political knowledge. This can probably be attributed to the fact that most of the research was conducted in the pre-social networking sites era. To test the hypotheses, two surveys in India were conducted in an election year in India. The preliminary survey (N = 492) conducted immediately before the election captured participants’ historical, civic and current knowledge. Structural equation modeling was used for analysis. While surveillance gratification and affiliation motivation were associated with information processing behavior, the latter did not predict political knowledge. Following this study, the battery of knowledge items was refined and new items were added. Following the general election, the main study (N = 1020) was conducted in two cities in India. The analysis found that surveillance gratification was associated with attention and elaboration and affiliation motivation was associated with elaboration. Attention to political content was significantly associated with political knowledge. In addition, the moderation analysis demonstrated that affiliation motivation moderates the path from attention to elaboration and attention to political knowledge. Individuals with a strong affiliation motivation are significantly more likely to elaborate on political content when they pay attention to it and they are also more likely to gain knowledge as a result of attention to such content. Finally, both surveys revealed that surveillance gratification and affiliation motivation were strongly correlated on Facebook. Therefore, the inference is that political knowledge accumulation in a socially networked world is socially driven. It can no longer be thought of as a purely cognitive process. Affiliation motivation serves as the primary motivation on Facebook and individuals with a strong affiliation motivation are likely to accumulate more knowledge when they stumble upon and attend to political content on the site. A third study examining the impact of CMM on political behavior was also conducted using regression analysis. Surveillance gratification, attention, elaboration and political knowledge were significant predictors of traditional political participation, while surveillance gratification, attention and elaboration predicted political activity on Facebook. Limitations and future directions are discussed.